Painful and recurring injection site reaction to alirocumab and evolocumab in a young woman with familial hypercholesterolemia and effective therapeutic alternative based on inclisiran: a case report - Allevi, Massimiliano; Sarnari, Silvia; Giulietti, Federico; Spannella, Francesco; Di Pentima, Chiara; Sarzani, Riccardo (Frontiers in Cardiovascular Medicine, 2023)
A 28-year-old woman with autosomal dominant familial hypercholesterolemia (FH) with a probable coexistent polygenic contribution causing very high low-density lipoprotein-cholesterol (LDL-C) levels, started therapy with the proprotein convertase subtilisin/kexin type 9-inhibitor (PCSK9i) alirocumab, in addition to high-intensity statin plus ezetimibe. Forty-eight hours after the second injection of alirocumab, the patient developed a painful palpable injection site reaction (ISR) that recurred after the third administration of the drug. Treatment was then switched to evolocumab, another PCSK9i, but the patient had an ISR with similar features. The most conceivable cause of the ISR was a cell-mediated hypersensitivity reaction to polysorbate, an excipient contained in both drugs. Although ISR after PCSK9i administration is usually transient and does not compromise the continuation of treatment, in this case the recurrence of such side effect in an exacerbated way led to treatment withdrawal, with a subsequent re-exposure to increased cardiovascular (CV) risk. As soon as it became available in clinical practice, the patient started treatment with inclisiran, a small interfering RNA targeting hepatic PCSK9 synthesis. No adverse events were reported after inclisiran administration and LDL-C levels decreased significantly, confirming the evidence that this innovative approach to hypercholesterolemia is a safe and effective resource in patients at high CV risk who cannot achieve LDL-C goal with conventional lipid-lowering therapies and antibody-based PCSK9i.